Restoring the eastern oyster: how much progress has been made in 53 years?. Issue 8 (3rd August 2018) - Bersoza Hernández, Ada; Brumbaugh, Robert D; Frederick, Peter; Grizzle, Raymond; Luckenbach, Mark W; Peterson, Charles H; Angelini, Christine
Abstract : Coastal ecosystem restoration is accelerating globally as a means of enhancing shoreline protection, carbon storage, water quality, fisheries, and biodiversity. Among the most substantial of these efforts have been those focused on re‐establishing oyster reefs across the US Atlantic and Gulf coasts. Despite considerable investment, it is unclear how the scale of and approaches toward oyster restoration have evolved. A synthesis of 1768 projects undertaken since 1964 reveals that oyster substrate restoration efforts have primarily been concentrated in the Chesapeake Bay and the Gulf Coast, have been heavily reliant on oyster shell, and have re‐established 4.5% of the reef area that has been lost across all regions. By comparing costs to ecosystem service benefits, we discovered that the return‐on‐investment of oyster restoration varies widely, but generally increases with project size. To facilitate the recovery of coastal ecosystems and their services, scientists and resource managers must adopt a new restoration paradigm prioritizing investment in sites that maximize economic and ecological benefits and minimize construction costs.